Olhares possíveis: comunicação e turismo em complexos urbanos transfronteiriços - Barretto, Ana Isaia (2018)
The construction of this thesis considers the existence of a structure of complementarity of the tourism in the Cross-border Urban Complex of the triple frontier that separates Brazil, Argentina and Paraguay. Therefore, it is explained how Communication contributes to the development of tourism practices in these environments, based on a qualitative exploratory approach of multiple cases, given the rare records of communicational studies in Tourism in the region. The empirical object of the Triple Border of Foz do Iguaçu (Brazil), Puerto Iguazú (Argentina) and Ciudad del Este (Paraguay) recognized as a Transboundary Urban Complex (DILLA ALFONSO, 2015) is identified, a notion that conceives the agglomeration of capital goods and people with relationships of local individuals or located in communities in transnational interaction. Several approach perspectives of Tourism, such as Chias (2007); Gastal (2001, 2002, 2003, 2005); Petrocchi (2007); Wainberg (2000, 2003), are considered due to the fact that they ground the understanding of its communicational experiences. The cross-border condition is supported by authors who studied the Brazil-Argentina-Paraguay context, as Albuquerque (2010); Beliveau, Montenegro (2010); Lucena (2012); Rabossi (2010a, 2010b, 2011); Roseira (2006) and Silveira (2004, 2016). In order to develop the distinct notions necessary for this thesis, the Hermeneutics of Depth (THOMPSON, 1995, 2009) is chosen as the guiding method, aiming to: Conceptualize historical, geographic and tourist aspects of the three cities; Relate tourism trends and interfaces with communication in cross-border environments; To examine how the communication and tourist actions in Triple Border are configured through the institutional portals of the three cities and Identify/encode user/tourists comments about their experiences in the tourist attractions of the three cities. The CIDTUR methodological procedure (BARRETTO, 2011) is applied in the tourist institutional portals of the studied locations and aims to understand how they are structured. Understood as symbolic forms (THOMPSON, 1995), institutional tourist portals and user/tourists comments are analyzed and correlated with the concepts of Tourism and Frontier, searching for the recognition of probable scenarios and communicational actions. Institutional tourist portals become means with the possibility of ordering directions and, when confronted with the records of the Tripadvisor platform, it is noticed the establishment of a communicational network that evidences new dynamics within tourist practices, this one based on the production of content and in the relationship with the users. Its analysis in the context of the tourist potentialities in the Transboundary Urban Complex of Foz do Iguaçu, Puerto Iguazú and Ciudad del Este allowed, finally, to propose the concept of Tourist Communication Experiences.